Rancang Bangun Aplikasi Administrasi Kependudukan Berbasis Web Menggunakan Metode SDLC pada Desa Redamata - Maria Novani Ngailo; Andreas Ariyanto Rangga; Emirensiana D Ege (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The Village Office is the village administration center in rural areas. The function of the village government is to carry out village administration which is carried out by the village head, village officials and the village residents themselves. In Rada Mata Village, Tambolaka City District, Southwest Sumba Regency, it is one of the villages that already has internet access. The village makes it easy to access sites on the internet. Therefore, the aim of this research is to create a system capable of managing population information data. The results obtained from this research are a population information system that can solve the problems faced by Rada Mata Village. From the results of the discussion it can be concluded that the population information system can answer the problems faced, including making data searches easier and faster, archiving data does not take up a lot of space because it has been replaced by digital storage, and data reporting can be presented quickly, completely, attractively and appropriately. village needs.